Performance comparison of the Xamarin platform and native applications for Android operating system - Bodia, Ihor; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2017)
The article presents the results of comparative analysis of various tools for creating applications for the Android operating system. Performance analysis was based on applications created using individual frameworks, in particular Xamarin and native software development tools. Several research criteria have been defined, based on which results of performance comparison have been derived and formulated conclusions